2019
DOI: 10.3389/fenvs.2019.00141
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Groundwater Discharge: Updates on Its Measurement Techniques, Geophysical Drivers, Magnitudes, and Effects

Abstract: The number of studies concerning Submarine Groundwater Discharge (SGD) grew quickly as we entered the twenty-first century. Many hydrological and oceanographic processes that drive and influence SGD were identified and characterized during this period. These processes included tidal effects on SGD, water and solute fluxes, biogeochemical transformations through the subterranean estuary, and material transport via SGD from land to sea. Here we compile and summarize the significant progress in SGD assessment met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
166
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(168 citation statements)
references
References 258 publications
(349 reference statements)
2
166
0
Order By: Relevance
“…Submarine groundwater discharge (SGD) comprises terrestrially derived fresh groundwater and re-circulated seawater 1 3 . SGD can be affected by tidal pumping, wave set-up, currents, and density gradients 4 6 . In particular, under strong winds of 10 m s −1 (i.e., storms and typhoons), wave pumping rates can increase by orders of magnitude exceeding the rates of fresh water inputs from runoff and SGD 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Submarine groundwater discharge (SGD) comprises terrestrially derived fresh groundwater and re-circulated seawater 1 3 . SGD can be affected by tidal pumping, wave set-up, currents, and density gradients 4 6 . In particular, under strong winds of 10 m s −1 (i.e., storms and typhoons), wave pumping rates can increase by orders of magnitude exceeding the rates of fresh water inputs from runoff and SGD 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Sediment compaction can also drive SGD far from shore, but compaction-driven flow is limited to locations where sediment deposition rates are high (Sharp & Domenico, 1976), and this process is not pervasive enough to explain Ra enrichments in the Atlantic basin. Exchange of groundwater and seawater also occurs by processes variously referred to as hydrodynamic exchange (Wilson et al, 2016), benthic exchange (Huettel et al, 2014), or porewater exchange (Taniguchi et al, 2019). This type of flow includes wave-and current-driven flow processes and is most active in the upper 2-12 cm of sandy seafloor sediments (Huettel et al, 1996(Huettel et al, , 2014Jahnke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple driving forces for groundwater‐seawater exchange have been identified (Figure 1) (Moore, 1999; Robinson et al, 2018; Santos et al, 2012; Taniguchi et al, 2019). Tidal fluctuations and differences in hydraulic head between land and the ocean are the most recognized drivers for SGD along the shore.…”
Section: Introductionmentioning
confidence: 99%
“…Submarine groundwater discharge (SGD) is an important vector for the delivery of nutrients to the coastal ocean (e.g., Taniguchi et al, 2019). While once thought to be a relatively minor component of the overall coastal nitrogen budget, studies have shown that non-point-sources of diffuse SGD can supply as much nitrogen into coastal waters as rivers (Slomp and Van Cappellen, 2004;Kroeger and Charette, 2008;Rodellas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%